Development of sports injury awareness programs for athletes and coaches. Issue 4 (27th March 2011) - Kotila, K; Andersen, B; Kirkegaard, L
Abstract : Background: Approximately 2.7 million Danes are active in sports and leisure activities. In 2009 over 100.000 sports injuries were registered as medically attended sports injuries in Denmark. National Olympic Committee and Sports Confederation of Denmark and The Association of Danish Sports Physiotherapists have identified the need for increasing the level of awareness about sports injuries and rehabilitation among Danish citizens. Objective: The objective of the project is to focus on acute treatment and effective rehabilitation among Danish citizens in order to shorten the period of inactivity and lessen the risk of new injuries. Design: Four elements are initiated; 1.campaign in written and digital media, 2.website 3.application for smart telephones and 4. web-based e-learning program. Setting: The target group is Danish athletes and citizens in organised or unorganised sports. Intervention period: The campaign is launched in February 2011, by which date it will be possible to download the 'first aid on acute sports injury' application, acquire information on the sports injury homepage and attend the e- learn course. Main outcome measurements: The success of the project will be measured by the number of downloaded smart telephone-applications, the number of hits on the sports injury homepage, and by the amount of coaches finishing the e-learn courses by 2012. The level of awareness will be measured in a randomised phone interview among Danish athletes, citizens and physiotherapist. Conclusion: Awareness of proper treatment and rehabilitation can shorten the period of injury-based inactivity for the injured. The project will provide us with the knowledge about whether the four initiated elements are effective ways of increasing awareness in regard to sport injuries and effective rehabilitation. In the long term we hope to see less injuries, better first aid treatment and more effective rehabilitation and prevention, so Danish citizens can shorten the period of injury-based inactivity.